Self-assessment of the characteristics of nurses' work environment and psychometric analysis of the Slovene-language version of the Practice Environment Scale of the Nursing Work Index (PES-NWI) - Skela-Savič, Brigita (Obzornik zdravstvene nege, 2024)
ntroduction: Measures to improve nurses' work environments include ensuring adequate staffing levels, recognising the importance of nursing work, involving nurses in decision-making processes, and improving interprofessional communication. The aim of this study was to analyse the job characteristics reported by nurses and their association with the dimensions of clinical practice environments in hospitals. Methods: A cross-sectional explorative research design was employed. The Slovene-language version of the Practice Environment Scale of the Nursing Work Index (PES-NWI(SI)) and data on nurses' job characteristics were used. A total of 1,010 nurses (403 general care nurses and 605 healthcare assistants) from ten Slovenian general hospitals participated in the study. Permission to conduct the research was granted by the Commission of the Republic of Slovenia for Medical Ethics.Results: The mean score of the PES-NWI(SI) was low (2.64), and the scale reliability was 0.937. The original theoretical five-factor structure was confirmed. The regression model explained the five factors in 26–47% of cases. The explanatory variables included opportunities for advancement, educational opportunities, professional status, satisfaction with current job and work environment, independence at work, and study leave. Discussion and conclusion: The study revealed managers' inadequate ability to ensure sufficient staffing, insufficient involvement of both respondents and managers in hospital affairs, and the lack of promotion opportunities. Creating an optimal work environment for nurses is an important task for managers and leaders. National healthcare policy must consider nurses as equal healthcare professionals and nursing as both a professional and scientific discipline.
Keywords: career; interprofessional collaboration; job satisfaction; kariera; leaders; medpoklicno sodelovanje; nursing care; poklicni status; professional status; vodje; zadovoljstvo pri delu; zdravstvena nega